Mode-locked YDFL using topological insulator bismuth selenide nanosheets as the saturable absorber - Hazlihan Haris; Malathy Batumalay; Tan, Sin Jin; Arni Munira Markom; Ahmad Razif Muhammad; Sulaiman Wadi Harun; Megat Muhammad Ikhsan Megat Hasnan; Ismail Saad (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Fiber lasers have long remained relevant for various applications worldwide in many industries. This paper presents a mode-locked ytterbium-doped fiber laser (YDFL) using our home-made topological insulator Bi2Se3 nanosheets (TI Bi2Se3) as the saturable absorber. The fabricated TI Bi2Se3 is transported to the end of the fiber ferrule using an optical deposition process, which is a key ingredient for initiating a pulsed fiber laser. With a pump power of 211.1 mW, the captured repetition rate and pulse width are 8.3 MHz and 6.2 ns, respectively. The length of the setup configuration is approximately 20 m, which corresponds to an output power measurement of 12.4 mW with a calculated pulse energy of 1.5 nJ. There are no significant Kelly sidebands, but the strong stability of the pulsed laser is defined by a high signal-to-noise ratio (SNR) of around 60.35 dB.